2010
DOI: 10.1364/oe.18.025702
|View full text |Cite
|
Sign up to set email alerts
|

Critical coupling in dissipative surface-plasmon resonators with multiple ports

Abstract: We theoretically investigate resonant absorption in a multiple-port surface-plasmon polaritons (SPP) resonator near the condition of critical coupling at which internal loss is comparable to radiation coupling. We show that total absorption is obtainable in a multiple-port system by properly configuring multiple coherent lightwaves at the condition of critical coupling. We further derive analytic expressions for the partial absorbance at each port, the total absorbance, and their sum rule, which provide a non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
71
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(74 citation statements)
references
References 23 publications
0
71
0
3
Order By: Relevance
“…Finally, the resistive damping rate can be obtained from where tot is the total damping rate and res , rad are the resistive damping rate and radiative damping rates, respectively. The absorbance at angular frequency is given by [63] = 4 rad res…”
Section: Additional Gratingmentioning
confidence: 99%
“…Finally, the resistive damping rate can be obtained from where tot is the total damping rate and res , rad are the resistive damping rate and radiative damping rates, respectively. The absorbance at angular frequency is given by [63] = 4 rad res…”
Section: Additional Gratingmentioning
confidence: 99%
“…Thus, the coherent perfect absorber (CPA) concept was proposed by Chong et al to achieve photonic resonance in semiconductor Fabry-Pérot cavities [3]. At about the same time, it was shown by theoretical analysis of a metal grating undergoing plasmonic resonance that total absorption is obtainable in a multiport system by properly configuring input coherent light waves at critical coupling [4]. In ideal CPA devices, two or more input waves totally couple to a single-resonance state and undergo perfect absorption by the intrinsic loss associated with that state.…”
Section: Introductionmentioning
confidence: 99%
“…In ideal CPA devices, two or more input waves totally couple to a single-resonance state and undergo perfect absorption by the intrinsic loss associated with that state. Thus, it was found that complete absorption can be achieved using multiple beams incident on a lossy device such that interference of outgoing beams results in zero outgoing power [3], [4]. As coherent absorbers do not require nonlinear effects to actively modulate light intensity [5], they can be used as low-power active devices such as compact optical switches, modulators, and light-electricity transducers [3]- [7].…”
Section: Introductionmentioning
confidence: 99%
“…Corresponding to the time reversal of laser emission processes, coherent incoming optical fields in a CPA system are completely trapped into a resonance mode producing a null outgoing field due to destructive interference between the different coupling pathways. This coherent trapping effect is highly controllable with phase differences between the multiple incoming fields, providing ultrafast and low-power schemes for optical modulators, switches, and coherence filters [3].In pursuit of practical device applications, various CPA configurations have been suggested and experimentally demonstrated using surface-plasmonic resonance gratings [4,5], metamaterial absorbers [3,6], graphene monolayers with appropriate patterns, and additional resonant photonic thin-films [7,8]. By exploiting the CPA effect for all-optical active elements in photonic integrated circuit platforms, Bruck and Muskens theoretically investigated silicon-on-insulator waveguide systems loaded with plasmonic nanoantennas [9].…”
mentioning
confidence: 99%
“…In pursuit of practical device applications, various CPA configurations have been suggested and experimentally demonstrated using surface-plasmonic resonance gratings [4,5], metamaterial absorbers [3,6], graphene monolayers with appropriate patterns, and additional resonant photonic thin-films [7,8]. By exploiting the CPA effect for all-optical active elements in photonic integrated circuit platforms, Bruck and Muskens theoretically investigated silicon-on-insulator waveguide systems loaded with plasmonic nanoantennas [9].…”
mentioning
confidence: 99%